An engineering approach to roof top gardening - Abhinav Dubey; A.R. Radhakrishna (Annals of Agricultural Research, 2022)
With the growing demand for vegetables and fruits in this world of urbanisation roof top gardening finds an unavoidable place. The roof top gardening involves greater engineering application majorly in design of roof, irrigation management, arrangement of pots, waste management, moisture proofing etc. These factors contribute significantly in designing an effective roof top garden. Various problems faced in the engineering intervention were identified and suitable remedies were suggested in the research using a case study approach of roof top gardens in Bengaluru.A well maintained roof top garden is a positive sign of a healthy household.